Shear slotted bolted connection. (15th September 2016) - Nikoukalam, Mohammad T.; Mirghaderi, S.R.; Dolatshahi, Kiarash M.
Summary: Slotted bolted connections (SBCs) have been developed and used as an axial friction damper in braced frames since 1980s. To employ the benefits of SBCs in moment resisting frames (MRFs), rotational slotted bolted connections have been developed more recently with limited application in members that flexural behavior is dominated to shear. In this paper, shear slotted bolted connection (SSBC) is introduced as a new type of friction dampers to employ the benefits of SBCs in lateral load resisting systems with predominant shear behavior members that dissipate energy by traditional yielding mechanisms. The SSBC is a modified bolted connection that dissipates energy through friction in which friction is activated by shear force. The applications of the proposed system as a shear link in link beams of eccentrically braced frames (EBFs), in the beams of MRFs, and coupling beams of coupled concrete shear walls are introduced. To show the efficiency of SSBC, an existing EBF with tubular link beam is equipped with SSBC, and its behavior is studied via models created in general purpose finite element program ABAQUS (SIMULIA, The Dassault Systèmes, Realistic Simulation, RI, USA) verified thoroughly against relevant test results. Also, three MRFs with different beam lengths are modified using SSBC, and their monotonic and cyclic behavior are investigated using validated finite element models. The results show that, as expected, SSBC is capable of working as a mechanical shear fuse dissipating energy effectively in both MRFs and EBFs without any material yielding.